Perceptions on the impact of a structured community-based training model in undergraduate medical training during the first phase of clinical exposure: A qualitative study from Kerala - Shaliet Rose Sebastian; Geethu Mathew; Abel K Samuel Johnson; Avira Chacko; Bichu P Babu; Marina Rajan Joseph (Wolters Kluwer Medknow Publications, 2021)
The new competency-based undergraduate medical curriculum advocates early clinical exposure in medical training for adequate orientation to societal and patient needs. The present study aimed to explore the experiences of medical students about community-based training in rural hospitals during the first phase of clinical exposure. An exploratory qualitative study was conducted among 75 Bachelor of Medicine and Bachelor of Surgery students who underwent the training program as part of their undergraduate medical training using "most significant change" technique. The responses collected were analyzed using the inductive approach of thematic analysis. Majority of the participants opined that the program not only has enabled them to better understand their academic learning but also has provided a social learning experience. The student feedback throws light on the potential of such community-based learning programs to inspire the students to become a more humane version of themselves. This study observed that the remote hospital-based training has positively influenced the students.